Study Features Concerning the Mechanisms of Entrepreneurial Supply Chain Development - P. Belikova, Tamara; M. Lepeshkin, Sergey; Yu. Lepeshkina, Elena (International Journal of Supply Chain Management, 2020)
The role of supply managers in driving corporate performance is changing, with an increased emphasis on supply market intelligence, collaboration, inter-organizational partnerships, and operational integration with supply partners. The article presents possible approaches to the study of entrepreneurial supply chain activity manifestation and the development of entrepreneurship in general. In the framework of entrepreneurship supply chain development trend study, there is the need to analyze the state of various systems of society activity: political, social, and economic. On the basis of specific historical examples and statistical data summarized by the authors, they present the examples of entrepreneurial supply chain activity development in a changing system.